Editorial: Capacitating One Health in eastern and southern Africa - Richards, Shauna (CAB International, 2024)
This collection of case studies outlines the status of One Health in twelve countries in Eastern and Southern Africa considering four thematic areas: (i) research and innovation, (ii) governance, (iii) education, and (iv) implementation. The cases demonstrate each country’s results alongside their challenges and priorities for One Health.